The causes of delay in construction project in Kuantan - Nur Azuwa, Ghazali (2017)
The construction delays can be defined as the late completion of work compared to the planned schedule or contract schedule. Construction delays can be minimized only when their causes are identified. The objective of this study was to identify the causes delay in construction work in Kuantan, to study the effect of delays in construction project in Kuantan and to propose suitable risk management method to minimize the risk of project delay. A total of seven factors were contributed to the cause of construction delays, six effects from construction delays and eleven methods of minimizing construction delays were identified based on literature review. The questionnaire survey was distributed to the target respondent in sector government and private that involved in construction project in Kuantan. The process will be including five stages. The stages are including preliminary stage, reviewing stage, collecting data and information, analyzing data and make conclusion recommendation. The top three most important factors that contributed to the causes of delays were inclement weather condition, late in revising and approving design documents, delays in contractor's claim's settlement and labor productivity. Client-related delays were ranked the most significant groups that cause delays, followed by labor and equipment-related delays, and contractorrelated delays. Time and cost overrun were the common effects of delays in construction projects. To minimize delays in construction projects it has been identified by group of client, contractor, consultant and architect effective methods of minimizing construction delays includes: pay progress payment to the contractor on time because its impairs the contractor ability to finance the work, enough number of labor should be assigned and be motivated to improve productivity, reviewing and approving design document and reviewing and approving design document, producing design document on time and mistakes and discrepancy in design document have to take care off.